Analysis of DC distribution efficiency based on metered data in a typical Hong Kong office building - Qingye Yu; Sinan Li; Pengyuan Shen; Yuchen Ji; Kwok-shing Wong; Yiting Zhang (Energy Reports, 2022)
This paper aims to analyze the distribution efficiency of DC power distribution power system in commercial building based on measured data from a typical office building in Hong Kong. In this research, a real-scene comparative testbed was built in a Hong Kong office to compare the energy efficiencies of AC and DC power distribution system. Similar load characteristics and use schedules are set and used in the experiment. The distribution efficiency has been found to be affected by load type, voltage level and the loading conditions. The efficiency of this DC power system is derived, considering the PFC model was working in a good condition. For LED loads, the average distribution efficiencies after converter are 77.7% and 51.8 % under the condition of full lightning and normal lightning mode. The main loss in this system is transmission loss and switching loss. The average AC/DC converter efficiencies of LEDs are 92.21% and 88.85% respectively with the load working under full power and normal power, while the average AC power factors of LEDs are 85.31% and 56.22% respectively with the load working under the same as above. The average AC/DC converter efficiencies of the fan coil are 97.41%, 96.03%, 92.74%, 89.10%, 85.71%, 78.72%, 67.61%, 63.57% respectively with the load working under level 8 to level 1 while the average AC power factors of the fan coil are 98.0%, 99.0% and 99.4% respectively with the load working under low middle and high condition. As the PFC circuit does not have ideal power factor correction when the load is small, it is not recommended to add PFC circuit when the load power is low. Using uncontrollable rectifier circuit is going to lead to a better performance.